P139 The role of transcriptomic SMARCA4 expression in ovarian cancer biology. (1st November 2019) - Leitner, K; Wieser, V; Tsibulak, I; Degasper, C; Welponer, H; Knoll, K; Reimer, D; Wiedemair, A; Marth, C; Fiegl, H; Zeimet, AG
Abstract : Introduction/Background: The SWI/SNF complex - a chromatin remodelling complex - is recurrently mutated and inactivated in ∼20% of human cancers. Mutations of the SMARCA4 gene, which encodes the ATPase of the SWI/SNF complex, can be found in the majority of small cell carcinomas of the ovary, hypercalcaemic type (SCCOHT). EZH2 is the catalytic subunit of the PCR2 complex, which is an opponent of the SWI/SNF complex. EZH2 inhibitors could play a potential role in the therapy of SCCOHT. The aim of this study was to explore the role of SMARCA4 mRNA-expression in ovarian cancer. Methodology: SMARCA4 mRNA-expression was investigated in 20 non-neoplastic fallopian tubes and 276 ovarian carcinomas (OC) (including 144 high grade serous ovarian carcinomas, HGSOC) in relation to their clinical characteristics, p53- and BRCA1/2- mutational status, BRCA1/2 mRNA-expression and EZH2 mRNA-expression. Results: The SMARCA4 mRNA-expression in OCs was significantly higher compared to the control group (P<0, 001). There were no significant differences in SMARCA4-expression between the various histological subtypes. A subgroup-analysis of HGSOC showed higher SMARCA4-expression in patients younger than 65 years (P=0, 021), in patients without residual disease after surgical debulking (P=0, 008) and in patients with early FIGO stages I-II (P=0, 004). High SMARCA4-expression was associated with better progression-free survival (PFS) (P=0, 05) and better overall survival (OS) (P=0, 002). Patients with p53-mutations showed higher SMARCA4-expression (P=0, 004). There was a significant correlation between the expression of SMARCA4 and EZH2 (P=0, 000 r=0, 377). Multivariate Cox-regression model revealed independency of the prognostic value of SMARCA4-expression for OS in patients under the age of 65 years (P=0, 015). Conclusion: High SMARCA4-expression in patients with HGSOC is associated with younger age at onset of disease, early FIGO stage and with absence of residual disease after primary debulking. In patients younger than 65 years, high SMARCA4-expression is independently associated with better overall survival. Disclosure: Nothing to disclose.